An Analysis of Trends and Policies Promoting Alternative Fuel Vessels and Their Refueling Infrastructure in Europe - Gómez Vilchez, Jonatan J.; Julea, Andreea; Lodi, Chiara; Marotta, Alessandro (Frontiers in Energy Research, 2022)
In recognition of the contribution of navigation activities to greenhouse gas emissions, there are ongoing efforts in Europe to deploy zero- and low-emission vessel technologies. The main objective of this paper is to present an assessment of waterborne transport decarbonization in Europe by analyzing key policies and trends. In particular, the policy actions put forward by the European Union Member States and the United Kingdom between 2016 and 2018, including refueling infrastructure, the market evolution of alternatively-powered vessels and their techno-economic barriers are investigated. Our work focuses on electricity, hydrogen and natural gas. Our findings suggest that the policy and market responses to promote alternative fuel and electric vessels in Europe so far have been rather weak and lag behind the efforts exerted on road transport. Our conclusion is that, besides further research and development, more ambitious policy measures are needed to keep the prospect of waterborne transport decarbonization within reach in Europe.